The stokvel sector : opportunities and challenges - Townsend, Stephanie; Mosala, Thabo ([London] : SAGE, 2016)
By 2009, stokvels (community-based savings clubs) were playing a substantial role in the South African economy. A 2003 study entitled 'Stokvels: Making Social Cents', conducted by the University of Cape Town (UCT) Unilever Institute of Strategic Marketing, found that black adults in South Africa invested approximately R12 billion a year in stokvels, burial societies, mogodisanos and saving blocks. The UCT study revealed that, at the time, 2.5 million South African adults (that is 9% of the adult population of the country) - and one in every two black adults - belonged to a stokvel (burial societies excluded). One year earlier, a 2002 survey conducted by Futurefact had reported that there were 3.5 million stokvel members.
Originally Published in: Townsend, S., & Mosala, T. (2009). The stokvel sector: Opportunities and challenges. WBS-2009-5. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on May 5, 2016).
Keywords: elektronické knihy; electronic books; Rotating credit associations -- South Africa -- Case studies